EVALUATION OF THE HADITH IN TERMS OF SANAD AND CONTENT (EXAMPLE OF BUKHARI NARRATION) - TURAN, Mehmet (SSD Journal, 2025)
Discussions on the existence and value of women predominantly revolve around fundamental issues such as the ontological equality of men and women and the role of women in society and family life. The answers to these questions are shaped by beliefs, cultural codes, and social norms, varying across different cultures and societies. From the Islamic perspective, the value of women derives from their humanity, a principle supported by the Qur’an and Sunnah, which emphasize that men and women share the same essence of humanity. The creation process and worldly trial of both genders are evaluated on an equal footing. The Qur’an expresses the equality between men and women by stating that the deeds of every individual will be recompensed in full measure. In this context, the primary purpose of both men and women is to act with an awareness of servitude to Allah, striving to lead a life befitting human dignity, and to support one another as companions in the pursuit of Allah’s pleasure as the ultimate goal. To gain a deeper understanding of Islam’s perspective on women, it is essential to refer to the regulations in the Qur’an and Sunnah, as well as the narrative of creation.Whether women lack intellect and cognitive abilities compared to men is an important issue that has been discussed in philosophy, religion and social sciences for many years. Especially in Islamic thought, different views have been put forward on this issue through the interpretation of some hadiths. This study examines the origins of this debate in Islam and its reflections today. At the beginning of the study, the general position of women in Islam and the values attributed to women are emphasized. Then, the narrations interpreted as “women lack intellect” are analyzed with the methods of hadith science. By examining the hadith’s hadith script and content, the aspects that may be open to different interpretations were identified. The aim of the study is to evaluate such hadiths in their historical and cultural contexts and to prevent misunderstandings that are common today. In particular, in addition to the misunderstanding of hadith texts through literal reading, the importance of a holistic approach by taking into account the conditions under which the texts emerged is emphasized. For this purpose, the study first consulted the commentaries (explanations) in the works containing the relevant hadiths. In addition, various works, articles and researches written on this subject in the classical and modern period were examined. Video and internet sources on the subject were also included in the study, and the information obtained from different perspectives was brought together.